Using self organizing maps to analyze larval fish assemblage vertical dynamics through environmental-ontogenetic gradients. (5th September 2021) - Álvarez, I.; Font-Muñoz, J.S.; Hernández-Carrasco, I.; Díaz-Gil, C.; Salgado-Hernanz, P.M.; Catalán, I.A.
Abstract: We analyzed the influence of the stratification process in the vertical distribution of larval fish in a microtidal coastal Mediterranean zone. By applying a Self Organizing Maps (SOM) technique, we could analyze a complex dataset accounting for non-linear processes. The analysis integrated multivariate data on larval fish and environmental parameters in two depth strata through two-time components (nictimeral and fortnightly through the main spawning seasons), and considered size-based information. Although causal relationships cannot be constructed, the use of SOM analyses enabled the description of the whole system evolution overcoming the constraints of linear approaches in complex multivariate datasets with multiple dependencies in the data. We contend that this approach can help to unveil the intricate patterns of settlement/recruitment of young fish, which is often hampered by the rigidity of some formal statistical approaches. Highlights: Larval fish assemblages analysis with Self Organizing Maps allows overcoming linear constraints. Self Organizing Maps analysis allowed the description of the whole coastal multispecific system. Self Organizing Maps also allowed identifying ontogenetic differences in vertical positions. Differences in larval fish vertical strategies before & after the establishment of stratification.